Assembly of Indoline-2-carboxylate-Embodied Dipeptides via Pd-Catalyzed C(sp2)–H Bond Direct Functionalization - He, Yu-Peng; Zhang, Chao; Fan, Mengyang; Wu, Zhijie; Ma, Dawei (Organic letters, 2015)
Intramolecular dehydrogenative cyclization of 2-methoxyiminoacyl-protected phenylalanine derivatives proceeded at 110 °C under catalysis of Pd(OAc)2 in the presence of 1-fluoro-2,4,6-trimethylpyridinium tetrafluoroborate to afford substituted indoline-2-carboxylates that were converted into indoline-2-carboxylate-embodied dipeptides via Raney Ni-catalyzed hydrogenation.